Factors associated with the presence and prevalence of contagious ovine digital dermatitis: a 2013 study of 1136 random English sheep flocks - Dickins, Alan; Clark, Corinna C.A.; Kaler, Jasmeet; Ferguson, Eamonn; O’Kane, Holly; Green, Laura E. (Elsevier, 2016)
In 2013, a questionnaire was used to gather data on risks for introduction, and factors associated with prevalence, of contagious ovine digital dermatitis (CODD). There were 1136 (28.4%) usable responses from 4000 randomly selected sheep farmers in England. CODD was present in 58% (662) of flocks, with a reported prevalence of CODD lesions of 2.3%. The geometric mean period prevalence of all lameness was 4.2% and 2.8% in CODD positive and negative flocks respectively. Factors associated with a greater risk of presence of CODD were purchasing replacement ewes, not always checking the feet of sheep before purchase, not isolating purchased sheep, foot bathing returning ewes, foot trimming the flock more than twice in the year all compared with not doing these activities and increasing log10 flock size. Farmers who vaccinated sheep with Footvax™ were less likely to report presence of CODD. Factors associated with increasing prevalence of CODD lesions were not always checking the feet of purchased sheep, flocks that mixed with other flocks and sheep that left the farm for summer grazing and later returned. In addition, flocks where farmers followed the current recommended managements for control of footrot, had a lower prevalence of CODD whilst those who used foot bathing and where feet bled during routine foot trimming had a higher prevalence of CODD. The prevalence of CODD decreased with each log10 increase in flock size. We conclude that CODD is an infectious cause of lameness in sheep of increasing importance in GB. Introduction is linked to poor biosecurity with one likely source of the pathogen being introduction of or mixing with infected sheep. As with footrot, prevalence of CODD was lower in flocks where farmers focused on individual treatment to manage lameness and avoided foot bathing and trimming feet. We conclude that most of the currently recommended biosecurity and treatment approaches to control footrot in GB are also effective for control of CODD.